Domestic retrofit supply chain initiatives and business innovations: an international review - Brocklehurst, F; Morgan, E; Greer, K; Wade, J; Killip, G (Ubiquity Press, 2021)
A systematic review of international evidence on housing retrofit supply chains was undertaken for the UK government: a Rapid Evidence Assessment (REA) summarised the most relevant research from outside the UK; key emerging themes were examined via analysis of 10 expert interviews with European and UK stakeholders, selected for the depth and breadth of their experience in developing retrofit business models. Market development requires concerted efforts from industry and policy, including the regulation of minimum standards. Conservatism in the industry means that opportunities for retrofit will be ignored in preference for the less risky, more familiar repair, maintenance and improvement (RMI) market. Successful retrofit involves customer engagement and after-care, which is outside customary practice. Financing mechanisms are important for firms’ cashflow and for customer acceptance. Skills governance needs to take account of national vocational education systems, and is more complex than simply providing a few new courses. Local partnerships are needed to mobilise and organise the supply chain, whether through local government involvement or new business models enshrining collaborative quality assurance. More formal quality assurance implies some consolidation of supply chains. All these elements must be integrated into a service package, whose overall purpose is to minimise the risks of retrofit for supply chains and customers. Policy relevance A functioning, large-scale energy-efficiency retrofit market needs to have some of the attributes of the existing RMI market, with energy performance grafted on. When compared with the ideal requirements for effective policy, existing policy support is inadequate, being too short-lived, too inconsistent and too easily sidelined by market realities. Retrofit requires high-quality outcomes achieved through integrated service, but construction industry business culture is focused on inputs (not outcomes) and the service is fragmented. Policy must help deliver a cultural shift, which no country has yet succeeded in bringing about. The task may be slow as it entails coordination and change across policy, education and vocational training, and industry practices.